(3cJGH GdfUQI dePGgH GdYJQIs - (3CHh GdaVd LYaQ Hf CMeO Hf YHO GdSdGes
(3ChdgG (B:s
(3GdMeO ddg Ydi eG ef CeG HYO , abO hUd GdcJGH ef UGMHg eTJedkG Ydi aUhd SJI , QCjJ JaUjdgG dg s
(3BNQgG (B:s
(3hCeG eSGFd Gdabg haQhY GdTQY aEfG QCjfG JQc GdJYQV dgG dCf HGHgG QMH , hcd eLJgO ajgG eUjH Je hced s
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3HjQhJ , ecJHI GdMHjH GddeSi (B- (3HjQhJ (B((3Yde GdcdGe(B) s
Keywords: (3GdJhMjO hGdedd hGdfMds